Research of a Wheel-legged Obstacle Crossing Robot - Wang Yueqin; Tan Xiaolan; Ban Xiang; Li Dingyu; Yue Shidi (Jixie chuandong)
To meet the requirement of mobile robots to achieve high mobility and strong obstacle-crossing in complex and variable environment, a design scheme of passive transformable wheel-legged obstacle-crossing robot is proposed. The transformable wheel conversion process of the robot is obtained by external force operation, so no additional driver is required, which reduces the complexity of the mechanism. Firstly, based on the three-dimensional modeling of the whole robot, the structure, principle and force of the transformable wheel are analyzed, and then the structure optimization is carried out by taking the ratio of the triggering torque during the transformation process and radius before and after unfolding as the index. Afterwards, the force condition during the transformable stage of the robot is analyzed and the relevant parameters of the robot platform are adjusted to achieve stable obstacle crossing. Finally, kinematics simulation of transformation and obstacle-crossing process of the robot is carried out by using the Adams software, physical prototype is made and rationality of the structure design of the whole machine is verified by experiment.